Maria Colon of Marcos Yauri Montero: memory, writing and migration - Salazar Mejía, Nécker (2023)
Marcos Yauri Montero (1930) is a writer who belongs to the Peruvian Andean narrative. One of his novels is Maria Colon (1980), which deals with the refoundation of the Uco town after a flood that caused its destruction. The objective of this article is to analyze the status of the main characters of the Colon family according to the elements that define them in the course of the novel. For this purpose, a critical reading of the novel is carried out through the use of theoretical contributions related to memory, letter and migration. On the hand, Maria Colon seeks to recover the memory of Uco and refounds the town; in addition, Cayetano Colon writes a manuscript that narrates the history of Uco from the vision of the vanquished; finally, Zeferino Colon and Manuel Colon experience different degrees of migration that have, finally, the return to their homelands as their destination. The work concludes that Yauri Montero’s novel addresses thematic lines that are key to understanding the content of contemporary Andean narrative.